The Effect of Back Massage on Lower Back Pain in Intrapartum - Hotma Sauhur Hutagaol; Hanna Sriyanti Saragih (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2017)
Child birth is a painful and stressful event in a woman life which is accompanied with fatigue, fear and negative feelings and as labor proceeds, the state worsens (Mortavazi, 2012). The majority of pregnant women would prefer to experience labour without medical intervention, including pharmacological pain relief. The aim of this study is to analyze the effects of back massage to reduce lower-back pain in active phase of first stage of labour. A quasi-experimental design which involves both pre-test post-test control group design, an experimental group was used to study the effect of back massage intervention on first stage in intrapartum women and no intervention in control group. Data were analyzed Paired sample t-test was used to compare the pre-test and post-test data. Thus the hypotheses which stated that there is significant difference between the intervention group and the control group on were accepted. However, the hypotheses which stated that there is significant difference between the ntervention group and control group on hemoglobin levels were rejected. Thus, it can be concluded from the results of the present study that back massage has a significant effect in reducing back pain in intrapartum.